Race and Ethnic Relations in Canada - Li, Peter S. (Oxford University Press, 1999)
Race and Ethnic Relations in Canada was first published in 1990 by Oxford University Press as a collection of twelve original essays that provided a comprehensive overview of government policies and academic theories that affect the way race and ethnic relations are structured and interpreted in Canada. This second edition takes into account social changes and academic debates of the 1990s and updates materials and arguments in the original edition. The contributors, all leading Canadian sociologists and social scientists, discuss a wide range of topics, including theories of race and ethnicity, demographic trends, the 'vertical mosaic', immigration, multiculturalism, employment equity, policy on Native peoples, and language policy. The book is essential reading for understanding Canada's race and ethnic relations. –Publisher's description. Contents: Part 1: Introduction. Race and Ethnicity / Peter S. Li – Demographic Overview of Ethnic Origin Groups in Canada / Madeline A. Kalbach, Warren E. Kalbach. Part 2: Race, Ethnicity, and the State. Immigration, Diversity, and Minority Communities / Morton Weinfeld and Lori A. Wilkinson – State Policies and Practices as Racialized Discourse: Multiculturalism, the Charter, and Employment Equality / Frances Henry and Carol Tator – Altered State: Federal Policy and Aboriginal Peoples / James Frideres – The Multiculturalism Debate / Peter S. Li – Language Policy in Canada / Wilfrid Denis. Part 3: Perspectives on Race and Ethnicity. Revisiting the Vertical Mosaic: Occupational Stratification Among Canadian Ethnic Groups / Hugh Lautard and Neil Guppy – Studies of Ethnic Identity, Ethnic Relations, and Citizenship / K. Victor Ujimoto – Intergroup Competition in the Symbolic Construction of Canadian Society / Raymond Breton – The Political Economy of Race and Ethnicity / Vic Satzewich – Feminist Intersectional Theorizing / Daiva K. Stasiulis.
https://global.oup.com/academic/product/race-and-ethnic-relations-in-canada-9780195414776?cc=ca&lang=en&
Keywords: Canada; ETHNIC relations; Race relations

Chinese Immigrants on the Canadian Prairie, 1910-47 - Li, Peter S. (Canadian Review of Sociology/Revue canadienne de sociologie, 2008)
This paper examines the job histories of a group of first-generation Chinese immigrants who have been living in Canada from 50 to 70 years. The study focuses on the working experience of the Chinese prior to and during the exclusion era between 1923 and 1947, when they were barred from immigrating to Canada. The purpose of the analysis is to draw some general conclusions about the economic survival of an ethnic minority which has historically encountered severe discrimination and other structural barriers. The use of case histories in this study provides detailed insights into the organization of the working world of an immigrant group, and its incorporation into the Canadian economy.
https://onlinelibrary.wiley.com/toc/1755618x/1982/19/4